Karakteristik Faal Paru Berdasarkan Pemeriksaan Spirometri pada Pasien Suspek Tumor Paru dan Mediastinum - Pratiwi, Suryanti; Agus Setyawan, Ungky; Listyoko, Aditya; Kirana, Intan (Jurnal Klinik dan Riset Kesehatan, 2022)
Background: Lung malignancy is a lung disease that has the highest mortality rate in the world. An examination to determine the state of lung function is spirometry. Aim: This study aims to determine the distribution of lung function in patients with suspect of lung and mediastinal tumor at Saiful Anwar Hospital Malang based on age, sex, body mass index (BMI), and diagnosis. Methods: This research is a descriptive analytic, cross-sectional approach using medical record data from January 2018 to December 2019 and then the data would be processed by spearman test. Results: The results showed that patients with suspect lung and mediastinal tumors suffered the most in the age range of 51-60 years, the sexes were mostly male, the most diagnoses were lung tumors. Most of the interpretation results of the spirometry examination showed restriction, and normal body mass index. The results of the analysis of the relationship between pulmonary function descriptions had a p-value of 0.814 for diagnosis of suspected lung and mediastinal tumor, 0.003 for gender, and 0.360 for BMI. Conclusion: It can be concluded that there is a significant relationship between pulmonary function and gender and there is no significant relationship between pulmonary function with the diagnosis and BMI.